Partially blind proxy re-signature scheme with proven security - Xiaodong YANG; Chunlin CHEN; Ping YANG; Faying AN; Tingchun MA; Caifen WANG (Tongxin xuebao)
In order to solve the problem of anonymity and controllability of blind proxy re-signature,the concept of partially blind proxy re-signature was introduced by using the idea of partially blind signature.Furthermore,the security definition of partially blind proxy re-signature was also given.Based on the improved Shao scheme,a partially blind proxy re-signature scheme in the standard model was proposed.The proposed scheme allows proxy to add some public information negotiated by delegatee and proxy to re-signature.The scheme not only can achieve the transparent signature conversion from delegatee to proxy and protect privacy of message re-signed by proxy,but also prevented illegal use of re-signature.Analysis results show that the proposed scheme is correct,multi-use,partially blind and existentially unforgeable.It is more suitable for e-government data exchange system,cross-domain authentication system and so on.